The Influence of Augmented Reality (AR) Assisted Diorama Media on the Learning Outcomes of Third Grade Students in IPAS Metamorphosis Material - Ratna Dwi Astuti; Aulia Fajar Khasanah; Uci Ulfa Nur` Afifah (Journal of Practice Learning and Educational Development, 2026)
This study aimed to analyze the effect of augmented reality (AR)-assisted diorama media on third-grade students learning outcomes in Natural and Social Sciences (IPAS), specifically on the topic of metamorphosis, at MIN 2 Ngawi. This study employed a quantitativ approach using a quasiexperimental pretest and posttest control groupp design. The population and sample consisted of 43 students: 22 students from Class III A as the experimentaly group and 21 students from Class III B as the control group. A saturated sampling technique was applied. The research instrument was a multiplee-choice test whose validity, reliability, item difficulty, and discriminating power were examined. Of the 40 items tested, 28 were declared valid, and the Cronbach’s Alpha coefficient was 0.957. The data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, the homogeneity test, the paired-samples t-test, and the independent-samples t-test with the assistance of SPSS version 24. The results showed that the mean score of the experimental group increased from 60.91 to 86.59, while the mean score of the control group increased from 53.33 to 74.29. The t-test results indicated a significance value of p < 0.05. Therefore, AR-assisted diorama media had a significant effect on third-grade students IPAS learning outcomes on the topic of metamorphosis at MIN 2 Ngawi.